Zombie baseball beatdown - Bacigalupi, Paolo (Little, Brown and Company, 2013)
While practicing for their next baseball game, thirteen-year-old friends Rabi, Miguel, and Joe discover that the nefarious activities of the Delbe, Iowa, meatpacking plant have caused cows to turn into zombies.